O wielośredniej - Wilkowski, Andrzej (Multi-average, 2008)
We present bi-average in this paper. We also give example of bi-mode distribution. We define multi-average too, and its relationship with orthogonal polynomials.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 81-89